(untitled) (Global Journal of Management and Business Research, 2012)
This research examines the relationship of firm performance dependency on, strategic contribution, Personal credibility, HR delivery and business knowledge. This research has focused on RG pharmaceutical firm i.e. from Peshawar, Pakistan. Research analyzed the involvement of these four variables in performance of RG pharmaceuticals. Results show that there is significant relationship between RG performnce and strategic contribution, Personal credibility, HR delivery and business knowledge. Study use framework consisting of different variables and regression and correlation analysis of these variables is conducted to find relationship between dependent and independent variables. The knowledge from the results of this study serves as basis of recommendations for maximizing and help RG pharmaceuticals that how and which variable has more impact on it productivity. The result shows that the strategic contribution and HR delivery play vital role in the performance of RG Pharmaceutical.